PENGARUH MEDIA TAKALINTAR ( TABEL PERKALIAN PINTAR) TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS III SDN 19 SITIUNG - Suci Rahma Putri; Dwi Novri Asmara; Meri Mustika (STKIP Subang, 2024)
This research is based on the fact that Mathematics learning is still not optimal. Many student learning outcomes are below the KKM. Therefore, the researcher conducted a study using Takalintar media. The purpose of this study is to determine the effect of the use of Takalintar media on the mathematics learning outcomes of multiplication material students in grade I students of SDN grade III SD Negeri 19 Sitiung. This type of research uses a quantitative approach with the type of experimental research. The research design used in this study is Pre-Exsperimental Designs. The method used is One-Group Pretest Design type experimental research (initial test-final test). This research was conducted at SDN 19 Sitiung when this research was carried out in the second semester of the 2024 Academic Year, the sample in this study amounted to 20 students. Based on the results of the paired samples t test obtained a significance of 0.000<0.05, it can be concluded that there is an influence of Takalintar media on student learning outcomes in Mathematics multiplication material for grade III students of SDN 19 Sitiung. Takalintar media can be used by teachers to relate subject matter to the real world of students.